Zarządzanie logistyczne jako zorientowane na procesy logistyczne zarządzanie siecią dostaw - Mokwa, Marian (Logistics Management as Supply Chain Management Directed to Logistics Processes, 2009)
The aim of the article is to prove the thesis that: when we make the assumption that logistics management comprises: the activity creating general idea of logistics activities, which takes their process into consideration both in a firm and in their partners, multilevel and multidirectional coordination of logistics processes, the way of thinking which takes processes dependence and structural connections in a whole supply chain into consideration, and the purpose of these activities is improved customer service and increase in value of each firm and whole supply chain, then we have to do with supply chain management. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 320-328